2019
DOI: 10.1371/journal.pone.0214586
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effect of gentamicin on cell metabolism in three cultured mammary cell lines: “Are cell culture data skewed?”

Abstract: Many cells are cultured in media that contains an antibiotic to prevent bacterial contamination. Mycoplasma and other bacterial contamination is a serious problem for those involved in cell culture. Antibiotics in the media helps prevent this contamination and make life easier for the investigators; as performing cell culture experiments in antibiotic free media is difficult and requires vigorous sterile technique. There are many reports of antibiotics causing mitochondrial damage. In this study, we tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…I predict had they harvested mitochondria from cells not exposed to antibiotic cell culture media, results would have been even better. The damage to mitochondria caused by antibiotics and how the effect of antibiotics skews cell culture data has recently been published by us in PLOS one [23]. Therefore, for accurate cell culture data and healthier mitochondria for MOT antibiotics should be avoided.…”
Section: Discussion Conclusion and Future Directionmentioning
confidence: 99%
“…I predict had they harvested mitochondria from cells not exposed to antibiotic cell culture media, results would have been even better. The damage to mitochondria caused by antibiotics and how the effect of antibiotics skews cell culture data has recently been published by us in PLOS one [23]. Therefore, for accurate cell culture data and healthier mitochondria for MOT antibiotics should be avoided.…”
Section: Discussion Conclusion and Future Directionmentioning
confidence: 99%
“…Many cell lines are incubated in media containing antibiotics, such as gentamicin, penicillin or streptomycin, to prevent bacterial contamination. We found that gentamicin addition in routine culture media caused mitochondrial toxicity, increased mitochondrial ROS and changed cell metabolism [36]. There are many papers in the literature on the effects of antibiotics on metabolism of cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Some antibiotics may also present a significant influence on cell metabolism by inducing mitochondrial dysfunction and oxidative damage in mammalian cells. Taking this into consideration, cell culture studies on metabolism should probably be done in an antibiotic free media (Elliott and Jiang 2019 ). An example is the class of aminoglycoside antibiotics, which consists mainly of gentamicin and geneticin.…”
Section: Compounds Used For the Reprogramming Of Melanoma Cellsmentioning
confidence: 99%
“…They show diverse usability against prokaryotic and eukaryotic cells, especially due to the fact that cell response depends on its metabolism (Sobiepanek et al 2020c ). The addition of gentamicin in cell culture media inhibits: the mitochondrial membrane potential gradient in the cells, the upregulation of HIF1a gene expression, the glycolytic enzymes and glucose transporters as well as the increase of lactate production, induction of mitochondrial superoxide and the increase in the DNA oxidative damage in the cells (Elliott and Jiang 2019 ). The addition of geneticin (G418) may cause the change of glucose flux from glycolysis towards either the TCA cycle or other biosynthetic pathways in various cell lines like baby hamster kidney (BHK) and Chinese hamster ovary (CHO) cells (Yallop and Svendsen 2001 ; Yallop et al 2003 ).…”
Section: Compounds Used For the Reprogramming Of Melanoma Cellsmentioning
confidence: 99%